Waqoi’ Wa Ahdatsu Riwayah ‘Bishad Shindhu’ (Muhitu al-Huzni) Lil Adib al-Banghli Mir Musharraf Husain: Dirosah Aqdiyah - Muhammad Nure Alam (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2020)
Abstract:This research aims to demonstrate the importance of creed in human life. The creed is one of the pillars upon which the legislation of divine and non-divine religions relies. Most people act according to their beliefs and religious affiliations. The righteousness of people reflects through their beliefs and integrity of thinking. In this research, based on the analytical descriptive method, we have explored some of the creedal issues of Bangladeshi Muslims mentioned in the famous Bengali-Islamic novel